Splenic abscess caused by Propionibacterium acnes. - Gekowski, K. M. (Yale Journal of Biology and Medicine, 1982)
A 59-year-old male diabetic was admitted with an acute myocardial infarction and had recurrent. Propionibacterium acnes bacteremia. Fifteen months after the initial admission a splenectomy was required for removal of a large splenic abscess caused by P. acnes. Although this organism represents part of the normal skin flora, its presence of blood cultures requires serious evaluation since it may signify clinical disease, not merely contamination of blood cultures by skin flora.